Investigation of water motion in a fuel cell channel with a reservoir - Altintas, Arin Goksel; Celik, Erman; Karagoz, Irfan (Elsevier Sci Ltd, 2022)
This study presents a novel gas distribution channel configured with a reservoir and an extra outlet to prevent channels from being clogged by long slugs in the vicinity of the outlet port in fuel cells. The motion of water droplets in this channel was investigated using the volume of fluid method. The behavior of the water droplets in the channel is examined under varying outlet pressures, droplet size, the initial position of the droplets, and the direction of the gravitational acceleration. The results showed that the proposed design yields the water droplets to break up while preventing channel clogging and facilitating water removal. It has also been observed that water discharge accelerates as the reservoir outlet relative pressure decreases, and discharge occurs to a large extent when the gauge pressure is lower than-1000 Pa. The proposed intermediary water evacuation approach and design have been determined to have the capability of active water discharge from multiple points via an appropriate pressure differential. It is seen that liquid water propagation to larger areas, especially in long flow lengths, can be prevented via the proposed new design and approach.
Keywords: Water management; PEM fuel cell; VOF model; Water discharge; Droplet motion